The main approaches to the problem of self-organization and preparation of future teachers of technology (Pedagogy of Higher and Secondary Education, 2012)
Tsisaruk I. The main approaches to the problem of self-organization and preparation of future teachers of technology.In the article basic approaches open up to the problem of organization of independent work of future specialists, the role of independent work is analysed on practical employments of technological disciplines.
Keywords: independent work; practical employments; student; self-realization